Simulations in Pre-emptive and Preventive Intervention - Elif Gürdal Limon; Onur Limon (Güvenlik Stratejileri Dergisi, 2023)
Simulations are digital environments created by imitating real environments and creating similar ones with mathematical models. In this respect, it is possible to calculate all the possibilities that can be experienced by uploading the data of the real world to these imitated digital environments. The fact that the resulting knowledge can affect real-world policies is a subject that needs to be discussed. Thanks to simulations, probability calculations for important security issues of states have now become frequently used methods. However, it should be discussed whether this security method tried to be provided through the digital space will be a directing factor as a basis for defence or whether taking an action based on simulation data can be interpreted as an attack. This study undertakes to seek answers to these questions. The conceptual framework of the study is the concepts of pre-emptive and preventive intervention. In this context, the study examines whether the use of simulation data as a basis for defence in interventions can be a pre-emptive and preventive approach. The legitimacy of using simulation data and artificial intelligence analyses for identifying enemies and calculating aggression indicators depends on the specific forms of international cooperation and the processes through which international actors establish acceptable options.